Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Fisika Ulangan Tengah Semester Kelas XI MIPA - Ansita Diah Destiara; Dwi Teguh Rahardjo; Sri Budiawanti (Universitas Sebelas Maret, 2022)
This study aims: (1) to describe the profile of errors made by students of class XI MIPA 1 SMA Warga Surakarta in the academic year 2019/2020, (2) to analyze the profile of the causes of errors made by students of class XI MIPA 1 SMA Warga Surakarta in the academic year 2019/2020. The method used is a case study and was carried out in class XI MIPA SMA Warga Surakarta. The research subjects were selected as many as 8 students from 24 students of class XI MIPA 1 with a sampling technique aimed. Data collection techniques through observation techniques, taking data from test answer sheets, and interviews. Data validation was done by data triangulation, namely by comparing the data from the UTS results, the results of teacher and student observations, and data from interviews with several students. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion. Based on the data analysis and discussion, it was concluded: (1) the profile of errors made by class XI MIPA 1 SMA Warga Surakarta in solving physics questions for the mid-semester test of the 2019/2020 school year based on Newman's criteria were reading errors (3.84%), comprehension errors (20.18%), transformation error (50.23%), process skill error (58.65%), and encoding error (73.07%). (2) The reasons for errors experienced by students of class XI MIPA 1 SMA Warga Surakarta for the 2019/2020 school year are not being careful when reading questions, rushing to work on questions, forgetting material concepts, forgetting the equations used, and experiencing errors at this stage previously.